Locus- and domain-dependent control of DNA methylation at mouse B1 retrotransposons during male germ cell development - Ichiyanagi, Kenji; Li, Yungfeng; Watanabe, Toshiaki; Ichiyanagi, Tomoko; Fukuda, Kei; Kitayama, Junko; Yamamoto, Yasuhiro; Kuramochi-Miyagawa, Satomi; Nakano, Toru; Yabuta, Yukihiro; Seki, Yoshiyuki; Saitou, Mitinori; et al. (Genome Research, 2011)
In mammals, germ cells undergo striking dynamic changes in DNA methylation during their development. However, the dynamics and mode of methylation are poorly understood for short interspersed elements (SINEs) dispersed throughout the genome. We investigated the DNA methylation status of mouse B1 SINEs in male germ cells at different developmental stages. B1 elements showed a large locus-to-locus variation in methylation; loci close to RNA polymerase II promoters were hypomethylated, while most others were hypermethylated. Interestingly, a mutation that eliminates Piwi-interacting RNAs (piRNAs), which are involved in methylation of long interspersed elements (LINEs), did not affect the level of B1 methylation, implying a piRNA-independent mechanism. Methylation at B1 loci in SINE-poor genomic domains showed a higher dependency on the de novo DNA methyltransferase DNMT3A but not on DNMT3B, suggesting that DNMT3A plays a major role in methylation of these domains. We also found that many genes specifically expressed in the testis possess B1 elements in their promoters, suggesting the involvement of B1 methylation in transcriptional regulation. Taken altogether, our results not only reveal the dynamics and mode of SINE methylation but also suggest how the DNA methylation profile is created in the germline by a pair of DNA methyltransferases.